2021
DOI: 10.1002/hec.4364
|View full text |Cite
|
Sign up to set email alerts
|

Conflict exposure and health: Evidence from the Gaza Strip

Abstract: We study the impact of conflict exposure on health in the Gaza Strip using individual‐level longitudinal data and geo‐localized information on conflict‐related violent events. Results show that individuals living in localities exposed to more conflict events have a higher probability of suffering from a physical impairment and a chronic disease. Two mechanisms contribute to explain why living in conflict‐affected area increases the incidence of physical impairment: conflict increases the difficulty to reach he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Our analyses suggest that emotion-mediated behavior changes can spread the impact of crises into unrelated domains. Threats such as climate change, conflicts, pandemics, and natural disasters affect behavior directly by changing the costs of actions like going to work or to the doctor's office [50]. However, our findings suggest that-even beyond the fear of contracting COVID-19 a visit to a healthcare facility-these crises change behavior in ways that are not directly tied to the crisis and that may amplify problems in other important domains.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Our analyses suggest that emotion-mediated behavior changes can spread the impact of crises into unrelated domains. Threats such as climate change, conflicts, pandemics, and natural disasters affect behavior directly by changing the costs of actions like going to work or to the doctor's office [50]. However, our findings suggest that-even beyond the fear of contracting COVID-19 a visit to a healthcare facility-these crises change behavior in ways that are not directly tied to the crisis and that may amplify problems in other important domains.…”
Section: Discussionmentioning
confidence: 64%
“…An increase in the number of crises that humanity faces may generate emotional responses that affect decision-making in a host of important domains. Disease outbreaks and pandemics [45,46], climate change [47], political polarization [48], and conflicts [49,50] all evoke strong emotions and may affect decision-making in ways that are not clearly tied to the crisis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the number of crises that humanity faces may generate emotional responses that affect decision-making in a host of important domains. Disease outbreaks and pandemics [ 62 , 66 ], climate change [ 67 ], political polarization [ 68 ], and conflicts [ 69 , 70 ] all evoke strong emotions. The results from our study suggest that these crises may affect decision-making in other domains, which are not directly tied to the crisis.…”
Section: Discussionmentioning
confidence: 99%
“…In a small but nationally representative sample of Palestinian adults, Canetti et al 8 showed that screening for depression is positively associated with exposure to political violence and with greater loss of interpersonal and intrapersonal resources or the loss of a loved one. Focusing only on Gaza, several scholars examined the effect of exposure to conflict and violence on physical health 9,10 and revealed how people residing in areas where there are more instances of violence are more likely to have physical disabilities and chronic illnesses, in particular mental health issues, compared to others that have not experienced violence. These findings suggest that exposure to conflict and violence increases the risk of developing or maintaining depression.…”
Section: Literature On Depression and Conflictmentioning
confidence: 99%